2022
DOI: 10.3138/jammi-2022-0012
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of antimicrobial prescribing practice, knowledge, and culture in three teaching hospitals

Abstract: BACKGROUND: Antimicrobial resistance (AR) is one of the most critical threats to global health. One of its root causes, misuse of antibiotics, can stem from prescribers’ preconceived ideas, differing attitudes and lack of knowledge. Canadian data on this subject is scarce. This study aimed to understand the culture and knowledge of antimicrobial prescribing to optimize strategies targeting prescribers in the local antimicrobial stewardship program (ASP). METHODS: An anonymous online survey was developed distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In Canada, a similar study was conducted among antimicrobial prescribers including physicians, residents, and fellows in three teaching hospitals within the Université de Montréal network. The study revealed that the residents tended to choose a broader range of antibiotics (p < 0.001) [18]. Approximately 25% of participants were unaware of the presence of an ASP in their respective hospitals.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In Canada, a similar study was conducted among antimicrobial prescribers including physicians, residents, and fellows in three teaching hospitals within the Université de Montréal network. The study revealed that the residents tended to choose a broader range of antibiotics (p < 0.001) [18]. Approximately 25% of participants were unaware of the presence of an ASP in their respective hospitals.…”
Section: Discussionmentioning
confidence: 94%
“…These may in-clude workshops, seminars, webinars, and conferences focused on ASPs and antimicrobial stewardship. These platforms provide opportunities for healthcare professionals to share experiences, learn from experts in the field, and discuss challenges and solutions related to ASP implementation [18]. Furthermore, incorporating ASP education and training into the curriculum of medical and healthcare-related educational programs can help instill the principles of antimicrobial stewardship from the early stages of professional development.…”
Section: Discussionmentioning
confidence: 99%